KEMBALINYA SURGA FIRDAUS: MENILIK KEMERDEKAAN INDONESIA MELALUI PANDANGAN ‘ALI AḤMAD BĀKATHĪR DALAM DRAMA ’AUDAT AL-FIRDAUS - Rokib, Mohammad (Universitas Negeri Surabaya, 2016)
Ali Ahmad B?kath?r was a prolific Arab playwright, novelist and poet of the 20th Century. He wrote almost fifty literary works and more than thirty plays in Arabic which developed Islamic character in Arabic literature. His works sought to establish Islamic values and traditions that occurred in Islamic societies. Although his works contributed immensely to the Arabic and Islamic literature, B?kath?r has received lack of attention from scholars both in Islamic world and in non-Islamic world. This paper explores the Muslim effort in acquiring national independence on the literary works of B?kath?r, particularly on the concept of nationalism. In the process of acquiring national independence, Indonesia?s figures usually utilized the paradigm of nationalism through words of dialog. The words of figure that referred to nationalism will be discussed. In this paper, we argue that B?kath?r literary work?s ?Audat al-Firdaus contains the spirit of nationalism for gaining independence.